Meninjau Alasan Penyebab Cerai di Kabupaten Magelang - Logo Igo Karmed (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Divorce is something that is undesirable for every husband and wife. However, as time goes by, every family will experience great disagreements or conditions that make the decision to divorce a last resort. Divorce can only be done in front of a court hearing. The Religious Court is the judicial institution that has the authority to decide on these cases. As with marriage, divorce must also be based on strong reasons underlying the lawsuit. Through this research, the author and researcher hopes that the research results can be used as a reference or learning material regarding the reasons why someone sues their partner for divorce. This research was prepared using normative juridical methods which were presented descriptively and supported by literature study. This research was also prepared to explore the causes of divorce that occurred in Magelang Regency in 2023, whether divorce divorce or divorce lawsuits filed by husband and wife to the Mungkid Class IA Religious Court as an authorized court and in accordance with its absolute and relative competence.